A Study On The Applicability Of The Skills And Knowledge Of Software Professionals - Chooi, Kai Loon (2006)
This paper attempts to study the applicability of the skills and knowledge of software professionals. The results of this study found that software professionals were generally able to apply their knowledge effectively in their work.